Association between fluid intake and kidney function, and survival outcomes analysis: a nationwide population-based study. Issue 5 (12th May 2016) - Wu, Li-Wei; Chen, Wei-Liang; Liaw, Fang-Yih; Sun, Yu-Shan; Yang, Hui-Fang; Wang, Chung-Ching; Lin, Chien-Ming; Tsao, Yu-Tzu
Abstract : Objectives: Fluid intake, one of the most common daily activities, has not been well studied in chronic kidney disease (CKD) populations, and clinical outcomes are rarely addressed. The aim of this nationwide study is to explore the influence of daily fluid intake on cardiovascular and all-cause mortality and its association with renal function. Design: Observational cohort study. Participants: In all, 2182 participants aged more than 20 years participated in the Third National Health and Nutrition Examination Survey (1988–1994). Main outcome measures: Survival outcomes in patients with or without CKD, using multiple variable adjusted Cox proportional hazard models. Results: In a longitudinal survey with a median follow-up length of 15.4 years, 1080 participants died and 473 cardiovascular deaths were recorded. For all-cause mortality in the CKD group, individuals in the highest quartile of fluid intake (≧3.576 L/day) had better survival outcomes than those in the lowest quartile of fluid intake (≤2.147 L/day) (p=0.029) after adjustment of several pertinent variables. Conclusions: Although the interpretation of this observational study was limited by the failure to identify the compositions of ingested fluids, adequate hydration may offer some advantages in patients with CKD. However, the underlying pathophysiological mechanisms of the responses of normal and injured kidneys to chronic changes in fluid consumption warrant further investigation.